Vernacular Architecture - Hutt, Antony; Petherbridge, Guy T. (Islamic art and architecture in Libya, 1976)
Keywords: Architecture – Djebel Nefousa

Islamic art and architecture in Libya - Warfalli, Muhammad Salim Muqayyid (Libyan General Committee, 1976)
Forsatta, Wighu, Sharwas, Umm al-Tubul, Qasr al-Haj, Kabao, Nalut, Tombs of Holy Men, Mosques of JAbal Nafusa, Mosque of Ujlah
Keywords: Architecture – Djebel Nefousa

Libia Pittoresca : I Gsur berberi del Gebel Nefusa (Il Popolo del Friuli, 1939)
Keywords: Architecture – Djebel Nefousa; Récits de voyage – Djebel Nefousa

A History of Libyan Mosque Architecture During the Ottoman and Karamanli Periods 1551-1911. Evolution, Development and Typology - Masud, Ali (University of Michigan, 1979)
Keywords: Architecture – Djebel Nefousa

The Arabic Inscriptions on the Mosque of Abū Maʿrūf at Sharwas (Jebel Nefusa) - Lowick, Nicholas (Libyan Studies, 1973)
The medieval town of Sharwas – sometimes written Sharūs or Sarūs – figures in the writings of Ibn al-Warrāq (10th century A.D.), Ibn Hauqāl (10th century), al-Bakri (11th century), al-Idrīsi (12th century) and the anonymous author of the Kitāb al-Istibṣār (12th century). All are agreed that it was an important place, the chief settlement (umm qura) of the Jebel Nefusa. It had no congregational mosque (jāmic), but was one of the two towns in the Jebel provided with a minbār or pulpit. The name Abū Macrūf, as applied to the mosque and the surrounding ruins, does not appear in the medieval sources but certainly goes back many centuries in oral tradition. It refers to Abū Macrūf Wiyār ibn Jawād, a famous religious figure of the later 9th century who lived a short distance to the south-east of Sharwas and who was present at the battle of Mānū in A.H. 283/A.D. 896 - 7.A preliminary note on Sharwas and its mosque has already appeared in the Second Annual Report of this Society (pp. 10 - 11). There are no less than sixteen monumental inscriptions carved on separate blocks of stone outside and inside the Mosque. Most important for the dating of the structure is the two line inscription (no. 1, pl. VIa) in the tympanum of the west doorway. This is in the ornamented variety of Kufic usually referred to as ‘floriated’ The style is decidedly ‘provincial’ and does little credit to the engraver. Nevertheless it is possible to discern, in such features as the trifoliate ending to the dāl of waḥdahu in the first line, points of resemblance to the later of the two monumental inscriptions from Ajdābiyah published in the Society's Third Annual Report (p. 5, Pl. VIIIb). This is dated A.H. 351/A.D. 962. If it is true, as there suggested, that the floriated style was introduced into Libya between c. 922 and 962 A.D., then the inscription over the doorway at Sharwas is unlikely to be earlier than the second half of the the 10th century, allowing for the town's somewhat isolated position in the Tripolitanian hinterland. It may, indeed, be as late as the 12th century, if the present Mosque postdates the destruction of Sharwas, c. 1100.
Keywords: Architecture – Djebel Nefousa; Archéologie – Djebel Nefousa

Some Islamic monuments in Jabal Nafusa - Warfalli, Muhammad Salim Muqayyid (School of Oriental and African Studies (University of London), 1981)
It is a well-known fact that Libya is a country which has received very little serious study in the field of Islamic art and aroheaology. In Libya most research and study in art and archeaology has been centred on the Greek and Roman heritag+e$ and even the prehistoric era has received considerably more attention than the Islamic period. In the past ten years, howeverg excavations have been carried out in some Islamic sites both in the east and south of the country, yet so many other sites remain unexcavated and unsurveyed. The area of the Jabal Nafüsa is considered to be one of these important but neglected regions. The impetus behind this thesis, therefore, is to contribute to the present knowledge and it aims at paving the way for those who intend to go further by studying the remains of this area in greater detail. The other purpose of this thesis is to throw some light on some Islamic sites which should receive priority when carrying out excavations in the Jabal NaMsa. One obstacle that meets the scholar is to establish the historical background relative to the area of study. In the Jabal Nafüsa the historical information that we possess is scarce and sometimes obscure. This thesis contains an attempt to study the history of this area, especially concerning the first centuries of the Islamic era. Analogy and comparison were applied in order to form the historical background needed for studying some old Islamic monuments in the Jabal NafUsa. In chapters two, three and four, the emphasis is apparent on studying architecture and decorations. In the field of architecture a detailed study was applied to some Islamic remains in the area. These selected monuments reveal the variety of architectural features in the Jabal. Again comparative examples show the outaide influence on the Jabal and in addition architectural oharacteristics of local origin could be pointed out. The same method was followed when discussing the decorations which were found in some of the mosques mentioned. Comparison between these decorations and other similar dated examples made it possible to see the influence of other decorations found in different parts of the Islamic world. In chapter five the study of some mosques in Tmizda area has revealed new elements represented in the Christian and Roman influence on the Jabal. Chapter six is devoted to inscriptions which were found in various mosques in the Jabal Nafffsa. Comparative material helped in studying their style as well as suggesting an approximate date concerning the inscriptions of the Jabal. Finally this thesis could be considered as a humble attempt to illustrate some aspects of the Jabal Nafnsa, not only in respect to its importance in Islamic studies, but also in connection to other areas of study upon which some questions have been raised throughout the thesis.
Keywords: Architecture – Djebel Nefousa

Ricerche sui vari tipi di insediamenti trogloditici in uso Gebel Garian libico - Chiauzzi, Gioia (Atti Accademia Ligure di Scienze e Lettere, 1960)
Keywords: Architecture – Djebel Nefousa

Some mosques of the Jebel Nefusa - Allan, J. W. (Libya Antiqua, 1972)
Keywords: Architecture – Djebel Nefousa